Molecular Subtyping in Cholera Outbreak, Laos, 2010 - Noikaseumsy Sithivong; Tomoko Morita-Ishihara; Arounnapha Vongdouangchanh; Traykhouane Phouthavane; Khampheng Chomlasak; Lay Sisavath; Bouaphanh Khamphaphongphane; Bounthanom Sengkeopraseuth; Phengta Vongprachanh; Onechanh Keosavanh; Kongmany Southalack; Lee Jiyoung; et al. (Emerging Infectious Diseases, 2011)
A cholera outbreak in Laos in July 2010 involved 237 cases, including 4 deaths. Molecular subtyping indicated relatedness between the Vibrio cholerae isolates in this and in a 2007 outbreak, uncovering a clonal group of V. cholerae circulating in the Mekong basin. Our finding suggests the subtyping methods will affect this relatedness.